Exercise-Induced Cognitive Decline: Exploring the Role of Pain Catastrophizing - Johnston, Madison L. (My University, 2024)
The relationship between exercise and cognition has been extensively studied, with results varying based on factors such as the length, intensity, and modality of exercise and the timing, task, and domain of cognition under investigation. While studies evaluating concomitant exercise and cognition overwhelmingly indicate decrements in performance on executive function tasks at high intensities, there remains limited agreement on how individual differences or cognitions might affect the physiological processes linked to these declines. As such, the present prospective, within-subjects study sought to systematically examine the impact of pain catastrophizing, a variable known to impact attentional processes, on the relationship between exercise intensity and executive function. Following completion of a series of online questionnaires and familiarization procedures (Visit 1), eligible participants completed an executive function test, the Cedar OWAT, while simultaneously completing a graded maximal exercise test on a treadmill (Visit 2). Results indicated significant decrements in executive function performance as exercise intensity increased, with pain catastrophizing interacting with exercise intensity to exert differential effects on hit rate and precision. In summary, the present study replicates previous findings demonstrating a significant negative relationship between exercise intensity and executive performance and offers initial evidence that higher levels of pain catastrophizing could contribute to complex alterations in cognitive performance under such conditions. These findings should be further explored in future studies, as they might hold particular relevance in settings in which maintaining peak cognitive abilities is crucial for effective decision-making, performance, and overall health.
Keywords: executive function; pain catastrophizing; exercise intensity; performance